Influence of Taylor waves on standing windows of oblique detonation wave. (March 2020) - Cui, H; Gui, M Y; Zhang, L Y; Zhang, H
Abstract: An oblique detonation wave stabilized over a body has been studied due to the ongoing development of high-speed propulsion systems, such as oblique detonation wave engines and ram accelerators. Standing window of oblique detonation wave reflects the degree of standing difficulty. Firstly, Shock relations coupled with chemical equilibrium are solved to draw detonation polar diagrams between oblique detonation angle and wedge angle by iterative algorithm. In these diagrams, the wedge angle detaching from the wedge nose is referred as the maximum wedge angle θιηॉκ and forming CJ detonation in the direction normal to the oblique detonation wave is referred as the minimum wedge angle θख़τ. The region between the two wedge angles is regarded as the standing windows. G. Emanuel holds that Taylor waves follow the oblique detonation wave as the wedge angle is smaller than θख़τ. Based on reactive Euler equation, wedge-induced oblique detonation is simulated in this paper. For the case of the wedge angle below θख़τ, Taylor waves change post-detonation wave flow field to maintain standing oblique detonation wave. Therefore, the standing window becomes wider.